Unmasking chloride attack on the passive film of metals - B. Zhang (Nature Portfolio, 2018)
Collecting experimental evidence of chloride ion attack on protective passive metallic films due to corrosion remains challenging. Here, the authors show that the boundaries between nanocrystals and amorphous regions in the passive film ease chloride transport even as they do not coincide with areas of high chloride concentration.